Antimicrobial Activity of Cinnamon, Tea Tree, and Thyme Essential Oils Against Pathogenic Bacteria Isolated from Tilapia (Oreochromis spp.) in Aquaculture Farms - Karen A. Terrazas-Pineda; Liliana Alamilla-Beltrán; Claudia Ariadna Acero-Ortega; Juan Antonio Damas-Espinoza; Georgina Calderón-Domínguez; Rosalva Mora-Escobedo; Vicente Vega-Sánchez; Fabián Ricardo Gómez-de Anda (Molecules)
Overexploitation has led to a rise in pathogenic bacteria within aquaculture, increasing reliance on antibiotics, and developing microorganism resistance. This situation underscores the need to explore alternatives with a reduced ecological impact. Metabolites derived from essential oils have demonstrated antimicrobial properties that can inhibit or diminish the activity of various microorganisms. In this study, the antimicrobial efficacy of cinnamon (Cinnamomum zeylanicum), tea tree (Melaleuca alternifolia), and thyme (Thymus vulgaris) essential oils against pathogenic bacteria (Aeromonas, Pseudomonas, Shewanella, Comamonas, Vibrio, Acinetobacter, and Empedobacter) isolated from tilapia (Oreochromis spp.) brooded in Hidalgo State, Mexico, were investigated. Diffusion tests were conducted using discs infused with 12 different antibiotics and discs infused with essential oils at concentrations of 15, 10, and 5 μL each. Minimal inhibitory concentration tests were performed using a 96-well microplate format. All bacterial strains exhibited multi-resistance to various antibiotics; however, thyme and cinnamon effectively inhibited the tested bacteria at the lowest concentrations, while tea tree oil was the least effective. The findings suggest the potential incorporation of thyme and cinnamon as an alternative prevention to decrease the use of antibiotic treatment.